(untitled) (Pakistan Journal of Kidney Diseases, 2025)
. Introduction: Hospital acquired infections are becoming a major concern for health care providers and especially nephrology patients where a lots of interventions and frequent admissions are observed. Objective of this study was to evaluate one of the emerging multidrug resistant enterococcus organisms with significant healthcare implications. Methods: This was a retrospective study evaluating the isolates from different samples from May 2018 to Sep 2019. All isolates growing enterococci were identified and evaluated for sensitivity pattern. Results: Out of 1500 samples 86 cases of Enterococci were isolated and 8 samples had resistance to Vancomycin. 2 isolates were also resistant to linezolid. Conclusion: Vancomycin resistance among Enterococci isolates is a major concern for health care providers dealing with complex and prolonged hospital stay patients. Furthermore, the emergence of Linezolid resistance is a cause of concern highlighting the judicious use of antibiotics.